Isotope hydrology and paleohydrology of the Slave River Delta, NWT - Benkert, Bronwyn (University of Waterloo, 2010)
Water isotope tracers and multi-proxy paleolimnological approaches are used to characterize the present and past hydrology of the Slave River Delta (SRD), NWT. This research addresses crucial gaps in knowledge about the role of major hydrological processes on the water balances of northern freshwater lakes, and responds to concerns expressed by local land users about declining flood frequency in the delta following upstream river regulation. Contemporary hydrological studies were conducted using multiple lakewater sampling campaigns from a suite of 41 delta lakes situated in three previously recognized biogeographical zones - outer delta, mid-delta and apex – that were initially sampled in fall 2002, and again immediately following the spring melt, during summer, and in the fall of 2003-2005. Paleolimnological studies aimed at reconstructing flood frequency in the Slave River focus on a sediment core obtained from a flood-susceptible lake in the active delta. Together, contemporary and past studies of SRD hydrology provide a detailed picture of environmental change and variability in an important northern freshwater ecosystem.